Adaptive environmental assessment and management: a new approach to environmental impact assessment - Jones, Michael L.; Greig, Lorne A. (New directions in environmental impact assessment in Canada, 1985)

Adaptive Management of Renewable Resources - Walters, C. J. (Macmillan Publishers Ltd, 1986)
The author challenges the traditional approach to dealing with uncertainty in the management of such renewable resources as fish and wildlife. He argues that scientific understanding will come from the experience of management as an ongoing, adaptive, and experimental process, rather than through basic research or the development of ecological theory. The opening chapters review approaches to formulating management objectives as well as models for understanding how policy choices affect the attainment of these objectives. Subsequent chapters present various statistical methods for understanding the dynamics of uncertainty in managed fish and wildlife populations and for seeking optimum harvest policies in the face of uncertainty. The book concludes with a look at prospects for adaptive management of complex systems, emphasizing such human factors involved in decision making as risk aversion and conflicting objectives as well as biophysical factors. Throughout the text dynamic models and Bayesian statistical theory are used as tools for understanding the behavior of managed systems. These tools are illustrated with simple graphs and plots of data from representative cases. This text/reference will serve researchers, graduate students, and resource managers who formulate harvest policies and study the dynamics of harvest populations, as well as analysts (modelers, statisticians, and stock assessment experts) who are concerned with the practice of policy design.

Compass and Gyroscope: Integrating Science and Politics in the Environment - Lee, Kai N. (Island Press, 1993)
In this original and far-reaching synthesis, Kai N. Lee explains that together science and politics can lead the waytoward the sustainable management of the world’s resources. Rigorous science can act as our compass, pointingus toward greater and more useful knowledge (adaptive management), and practical politics can serve as our gyroscope, keeping usbalanced between competing interest groups. Unlike some approaches to sustainable development, Compass and Gyroscope is refreshingly grounded in the realworld. Lee explains that sustainability cannot occur overnight, we have neither an adequate base of knowledgenor a reliable means of properly implementing and executing management plans. "Sustainable development is not a goal, not a condition likely to be attained on earth as we know it. Rather it is more like freedom or justice,a direction in which we strive..." Using the Columbia River Basin in the Pacific Northwest as a case study, Lee examines the successes andfailures of past and present management. He describes what has been learned, and explains how that experiencecan be applied to environmental management generally. Throughout, the author delves deeply into the theoretical framework behind the real-world experience, exploring how theories of science, politics, and cognitive psychology can be integrated into environmental management.

Adaptive environmental assessment and management - Holling, C. S. (International series on applied systems analysis, 1978)
Keywords: Ecology; Economic development; Environmental impact analysis; Environmental protection